Expression of bta-miR-222 and LHCGR in bovine cultured granulosa cells: Impact of follicle deviation and regulation by FSH/insulin in vitro - Santos, P. H. [UNESP]; Nunes, S. G. [UNESP]; Franchi, F. F. [UNESP]; Giroto, A. B.; Fontes, P. K. [UNESP]; Pinheiro, V. G. [UNESP]; Castilho, A. C.S. (Elsevier, 2022)
Final antral follicle development and future ovulation are mediated by gonadotropin-induced changes with spatio-temporally regulated expression of genes. Here, we aimed to quantify the relative mRNA abundance of bta-miR-222 and its predicted target, LHCGR, in granulosa cells (GCs) from follicles, after follicle deviation, as well as from GCs cultured in vitro with follicle stimulating hormone (FSH) and/or insulin. Thus, to study the impact of follicle deviation, Nelore heifers (n = 10; Bos taurus indicus) were hormonally synchronized and slaughtered 3 days after ovulation. Then, GCs from the dominant follicle (DF) and its respective subordinate follicle (SF) were recovered for RT-qPCR. For in vitro analysis, small follicles (2–5 mm) were dissected from bovine ovaries collected from a local abattoir. The GCs were isolated and cultured in serum-free medium, or treated with insulin (1 ng/mL or 10 ng/mL) alone or in combination with human recombinant FSH (1 ng/mL), for 6 days. Our findings showed that the relative mRNA abundance of LHCGR in GCs was higher in the DF compared to the SF (p = 0.01). Inversely, bta-miR-222 expression was lower in the DF compared to the SF (p = 0.01). Furthermore, GCs cultured with FSH and insulin together resulted in a higher abundance of LHCGR and a lower abundance of bta-miR-222 (p ≤ 0.05) when compared to GCs cultured with insulin alone. In conclusion, we found that the LHCGR upregulation in GCs from the DF is inversely related to bta-miR-222 expression. We also suggest the involvement of FSH in bta-miR-222 suppression in healthy bovine GCs.
Keywords: Antral follicle; Cattle; Follicle divergence; Gene expression; LHCGR; MicroRNA